Pengaruh Kondisi Lingkungan Keluarga Terhadap Kepatuhan Tata Tertib Siswa Kelas V SD Negeri 101796 Patumbak - Tri Ulina Br Sembiring (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2021)
This study aims to identify the influence of family environment conditions on the compliance with school rules among fifth-grade students at SD Negeri 101796 Patumbak. Using a correlational quantitative method, the research involved 54 students as subjects. Data were collected through questionnaires and analyzed using SPSS 22. The findings revealed a significant positive relationship between the conditions of the family environment and the students' compliance with school rules. Approximately 33.3% of the variance in rule compliance was explained by family environment variables. The study suggests the importance of family roles in supporting student discipline at school.